Design and evaluation of a dynamic job search website for non-literate users of Pakistan. Issue 4 (2nd October 2019) - Kalsoom, Aisha; Hussain, Syed Sajid; Khan, Iftikhar Ahmed; Nazir, Babar; Jadoon, Waqas; Khan, Imran Ali
ABSTRACT: Among the many available online job searching solutions, very limited are proposed for non-literate users. The available solutions have tested the possibilities using static web pages which are not applicable in the real world for non-literate users because of the dynamism of the real world. In this research, a dynamic job search solution is presented for non-literate users of Pakistan. User Interface (UI) requirements were identified through an extensive literature review. The culturally specific content in the form of hand-drawn sketches, voice feedback, semi-illustrations was identified and incorporated in the job seekers (non-literate) module. The same module was evaluated by the non-literate and semi-literate participants in a field study as per the usability specification defined by ISO-9241-11. The results have shown that non-literate users could search for a job efficiently in the minimum task completion time as compared to the time reported in the previous literature. They were satisfied and motivated to use the website again to search for jobs. The results indicate a potential for designing ICT-based solutions to provide services to the non-literate users in developing countries.